A SUSTAINABLE RAW RICE HUSK ADSORBENT FOR EFFECTIVE LEVOFLOXACIN REMOVAL FROM AQUEOUS SOLUTION: KINETIC, THERMODYNAMIC AND ISOTHERM STUDIES - Husham A. Atta; Khalid K. Hummadi; Mohanad J. M-Ridha (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Levofloxacin (LEV) is an important and widely used antibiotic. It is used to treat many bacterial infections. It may be found in water sources as a result of incomplete metabolism in humans and other sources. In this study, the adsorption of Levofloxacin by raw rice husk (RRH) was investigated. The effect of pH, time, temperature, RRH weight, and initial Levofloxacin concentration on the adsorption process were determined. Kinetic, isotherm and thermodynamic models were studied to explain the Levofloxacin adsorption mechanism on raw rice husk. The results of adsorption kinetics and isotherms revealed that the adsorption of LEV by RRH was better fitted with the Intraparticle model with coefficient of determination (R2=96%), while the Langmuir model represents the best isotherm model to describe the adsorption process with (R2 =95%). The removal efficiency reached 99% , the monolayer maximum uptake qmax is 2.47 mg/g and the adsorption intensity parameter (1/n) value is 0.763, which means that the adsorption is favorable. According to the thermodynamic coefficients, the adsorption process was spontaneous and feasible for the temperatures under investigation; the sorption efficiency was more favorable at higher temperatures, and the adsorption process is endothermic.